Implementación de una aplicación para gestión y seguridad del internet aplicando herramientas NET en los laboratorios de computo de la Universidad Técnica de Cotopaxi en el periodo académico marzo agosto del año 2013. - Lucero Pacheco, Nelson Leonardo (2014)
The present proposal of the Thesis is justified in the development of an application to secure the internet capable to control the disactivation and activation of the internet service in the computer laboratories of the Technological University of Cotopaxi. I have considered it essential for the development of the work, important themes such as internet, protocols. TCP/IP, proxy. And the PSP methodology, software ownership and the tools used for the development of the application, all this in order to understand better the points known and the be able to reach the established objectives, also for the rise of the information methodologies and technics of investigation were applied to demonstrate the hypothesis set through an analysis and interpretation of the results with which the same showed an application was developed. The idea is constituted principally that in the computer laboratories of the Technological University of Cotopaxi poses an application in a principal computer the same that in turn could through a friendly graphic interface provided to the operators of the laboratories, interns and extensionists activate and disactivate internet service of the computer laboratories that the operate, be it from machine to machine or by the quantity of computers that each one has, in other words collectively, this computer application was designed in the .Net tool that in turn contains the C# tool. That was developed through a PSP methodology. This computer application will solve the problems that have been taking place in the computer laboratories such as the incorrect use of a lot of computers.